Urgensi penerapan sistem pengendalian internal pada perbankan syariah di Indonesia - Husnia, Nidaul (Maliki Interdisciplinary Journal, 2024)
This research discusses the urgency of implementing an internal control system in Sharia Banking in Indonesia. The growth of Sharia Financial Institutions has experienced a rapid increase globally, especially in the Sharia Banking sector which is often in the spotlight. To avoid undesirable things in company operations, companies need to carry out audits. The main objectives of internal control are to guarantee the following: protection of public finances, achievement of predetermined goals and objectives, economical and effective use of resources and powers, accuracy and integrity of information, compliance with plans, rules, processes, laws , and regulations, as well as property protection.